Would You Pay an Insta-doctor a Visit? Social Media Personal Brands and Young Consumer Perception - Małgorzata Szwed (Journal of Marketing and Consumer Behaviour in Emerging Markets)
Technological developments and the broad availability of the Internet provide constant access to social media for users. These platforms are used to communicate with friends as well as to follow other users and brands. Also, physicians have public social media profiles on which they publish both professional and personal content. The objective of the paper is to explore and understand customers’ perception of physicians’ social media use. To obtain the purpose, a qualitative research method was adopted that involved 12 semistructured interviews with people who followed physicians’ profiles on social media. The study identifies three consumer groups: social media enthusiasts, sceptics, and those seeking authentic opinions, each with distinct attitudes toward physicians’ online presence. The findings emphasise that authenticity and consistency in personal branding are key to building trust and patient engagement. Social validation, through positive endorsements on social media, also significantly impacts consumer choices. The study highlights the need for tailored social media strategies in healthcare and suggests future research should address the ethical challenges and long-term effects of physicians’ online engagement. The research, focused on consumers’ perception of physicians’ social media presence, is novel. The results suggest directions for further research in the field of professionals’ personal branding on social media.